Community Network Development at the Indonesian Women's Empowerment Forum in South Bengkulu - Palenti, Citra Dwi; Ari Putra; Prayoga, Putri Regina; Gusti, Ririn (Journal of Nonformal Education and Community Empowerment, 2024)
The aim of this research is to determine the development of community networks at the Indonesian Women's Empowerment Forum (FPPI) in the Economic, Community, Cooperative and Entrepreneurship Program in South Bengkulu. The research method used was a qualitative method with a descriptive approach. Data collection techniques use interview, observation and documentation techniques. It was concluded that to increase empowerment in the FPPI program, the first thing to do was to provide education and training, which provides access to women to obtain education and skills training that is relevant to labor market needs and facilitates women's access to capital; business, loans and other financial services to support business initiatives as well as building support and mentoring networks that enable women to share experiences, skills and support in developing careers or businesses.